2020
DOI: 10.3389/fpls.2020.555572
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Nature of Interspecific Hybrid Sterility in Rice

Abstract: isogenic lines with various alleles/haplotypes and pyramided different alleles/haplotypes from sterile loci in the same genetic background aiming to study allelic and non-allelic interaction among different hybrid sterility loci in the AA genome species. Furthermore, the pyramiding lines ought to be used as bridge parents to overcome hybrid sterility for rice breeding purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…Genes with similar functions were observed in intersubspecific crosses in Oryza sativa , such as S5 [ 11 ], S7 [ 12 ] and S9 [ 13 ]. According to [ 27 ], in the cross between O. sativa and O. meridionalis , only pollen-killer genes have been reported. Li et al [ 23 ] performed linkage analysis of five pollen-killer genes: S51 located on chromosome 1, S52 and S53 located on chromosome 2, S54 and S55 on chromosome 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes with similar functions were observed in intersubspecific crosses in Oryza sativa , such as S5 [ 11 ], S7 [ 12 ] and S9 [ 13 ]. According to [ 27 ], in the cross between O. sativa and O. meridionalis , only pollen-killer genes have been reported. Li et al [ 23 ] performed linkage analysis of five pollen-killer genes: S51 located on chromosome 1, S52 and S53 located on chromosome 2, S54 and S55 on chromosome 7.…”
Section: Discussionmentioning
confidence: 99%
“…In the history of rice gene nomenclature, S with digits have been applied to the gene symbols of both pollen sterility genes and egg sterility genes. According to a database of rice, Oryzabase (Oryzabase.Available online: accessed on 31 December 2021) [ 31 ], and a recent review on hybrid sterility by Li et al [ 27 ], S56(t) is the latest gene symbol, which was found in the cross between O. sativa and O. glumaepatula , and caused pollen semi-sterility [ 32 ]. Therefore, we name the gene found in this study as HYBRID SPIKELET STERILITY 57 , with the gene symbol of S57 , following Yoshimura and Nagato [ 33 ] and McCouch and CGSNL [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to bivalents, univalents, trivalents, and tetravalents, as well as chromosome bridges and lagging chromosomes, were observed (Figure 3 and Table 5). Hybrid sterility can be caused by meiotic irregularities, chromosomal aberrations, or interactions between nuclear genes or between the cytoplasm and nuclear genes [33][34][35][36][37]. Although formation of the multivalents suggested some homologies between corresponding chromosomes as inferred from the monophyly of Suaveolentes species and a presumption that the species are allotetraploids derived from common ancestors [10,13,15,38], the univalents and multivalents, as well as chromosome bridges and lagging chromosomes, would lead to imbalanced chromosome segregation, resulting in hybrid sterility in crosses between N. benthamiana and N. excelsior.…”
Section: Discussionmentioning
confidence: 99%
“…Postzygotic reproductive isolation usually shows hybrid lethality, hybrid necrosis/weakness and hybrid sterility ( Baack et al, 2015 ; Ouyang and Zhang, 2018 ). In the past decades, about 50 loci related to reproductive isolation of the genus Oryza have been identified ( Ouyang and Zhang, 2013 , 2018 ; Guo et al, 2016 ; Li et al, 2020 ). In indica - japonica crosses, reproductive isolation usually shows hybrid sterility.…”
Section: Genetic Basis Of Indica - Japon...mentioning
confidence: 99%